Lactobacillus rhamnosus induces CYP3A and changes the pharmacokinetics of verapamil in rats. (1st November 2021) - Liu, Jie; Cheng, Yi; Zhang, Yuanjin; Huang, Shengbo; Liu, Zongjun; Wang, Xin
Graphical abstract: Highlights: Oral administration of L. rhamnosus decreased exposure of verapamil in WT rats. The interaction between L. rhamnosus and verapamil disappeared in Cyp3a1/2 KO rats. L. rhamnosus induced CYP3A activity and protein expression. L. rhamnosus altered the composition and assembly of gut microbiota. Abstract: Verapamil, a calcium channel blocker, has been approved as the first-line drug for treatment of angina pectoris, hypertension and supraventricular tachycardia. Lactobacillus rhamnosus, one of the normal strains in human intestinal tract, is very popular in the probiotic market for conferring a health benefit on the host. This report investigated the potential of gut microbiota-drug interactions between lactobacillus rhamnosus and verapamil via using wild type (WT) and Cyp3a1/2 knockout (KO) rats. In WT rats, administration of Lactobacillus rhamnosus for 14 days decreased systemic exposure of verapamil and increased its metabolite norverapamil in vivo, and resulted in gut microbiota-drug interactions. In Cyp3a1/2 KO rats, however, this interaction disappeared. Further studies found that Lactobacillus rhamnosus induced CYP3A activity and expression, and changed the composition of gut microbiota, thus changing the pharmacokinetics of verapamil. These results demonstrated the interaction between lactobacillus rhamnosus and verapamil, and indicated that the effect of gut microbiota on metabolic enzymes cannot be ignored.